Developing Medibang Paint-Based Digital Comic for Teaching Narrative Text - Hidayati, Khafidoh; Christanti, Ana (LPPM UNUSIDA, 2024)
This research is based on the limited use of English learning media, causing students to often get bored because of the monotonous learning atmosphere. This research aims to make learning more exciting and interactive by developing digital comic learning media based on Medibang Paint. This research uses the RnD (Research and Development) method using the ADDIE development model. The media expert validation results were 81.25% in the